Thermal Performance Enhancement With Melting Effect of Nickel Foam and MXene Nano-Enhanced Phase Change Material Composite-Based Thermal Energy Storages - Srivastava U.; Sahoo R.R. (My University, 2025)
This research explores the numerical investigation of melting processes in duplex and triplex tube latent heat thermal energy storage (LHTES) systems utilizing phase change material (PCM) enhanced with nickel foam and MXene nanoparticles. By incorporating a nickel foam/PCM/MXene (5% v/v) composite, the research scrutinizes the effects on melting characteristics, Stefan and Fourier numbers, and thermal behavior of both duplex tube thermal energy storage (DuT-TES) and triplex tube thermal energy storage (TrT-TES) configurations. A comprehensive analysis encompassing liquid fraction, melting temperature contours across varying melting durations, exergy destruction, exergetic efficiency, system efficiency, and the stored energy is conducted. The findings indicate that systems employing nickel foam/PCM-MXene composite exhibit superior performance compared to those utilizing nickel foam/PCM or pure PCM, resulting in a notable reduction in melting time. Furthermore, it is observed that the stored exergy of nickel foam/PCM composite surpasses that of pure cetyl alcohol PCM. In TrT-TES systems, melting with nickel foam/PCM composite occurs 58.82% faster than in DuT-TES systems. The stored energy of TrT-TES employing nickel foam/PCM and nickel foam/PCM/MXene composite is 4.55% and 3.69% greater, respectively, than that of DuT-TES systems. DuT-TES with nickel foam/PCM/MXene also achieves a 44.86% higher system efficiency at 90 s than nickel foam/PCM. Notably, the melting process with nickel foam/PCM/MXene in TrT-TES occurs 60.26% faster than in DuT-TES. Consequently, TrT-TES systems employing nickel foam/PCM/MXene composite demonstrate superior potential for latent heat thermal storage compared to DuT-TES systems. © 2025 by ASME.